Upaya Meningkatkan Disiplin Guru dalam Kehadiran Mengajar di Kelas melalui Penerapan Reward and Punishment - Muhamad Asnawi (Nusantara: Jurnal Pendidikan Indonesia, 2022)
Improving the quality of learning in madrasas depends on several factors. A very important factor, among others, is the application of madrasa culture towards quality improvement. Madrasa culture is a positive thing that must be maintained and implemented by all madrasa residents without feeling forced. One of the madrasa cultures that must be maintained is the issue of discipline, including the discipline of teachers in class attendance in the teaching and learning process. To improve the discipline of teachers can be pursued in various ways. This research is school action research. The action being tested is the application of reward and punishment for teachers at MAN Kendal. This research was carried out in two cycles, because from the results of research and data analysis, it turned out that in cycle II, teacher discipline in class attendance in the teaching and learning process increased and met the predetermined indicators of 75%. From the results of this study, it can be concluded that to improve teacher discipline in class attendance in teaching and learning activities can be done by applying reward and punishment to teachers.